Cell viability and protein turnover in nongrowing Bacillus megaterium at sporulation suppressing temperature - Kucerová, H; Strnadová, M; Ludvík, J; Chaloupka, J (Folia microbiologica, 1999)
In Bacillus megaterium, a temperature that suppresses sporulation (43 degrees C) only slightly exceeds both the optimum growth temperature and the temperature still permitting sporulation (40-41 degrees C). Here we show that, when cells grown at 35 degrees C and transferred to a sporulation medium, were subjected to shifts between 35 degrees C and the sporulation suppressing temperature (SST, 43 degrees C), their development and proteolytic activities were deeply affected. During the reversible sporulation phase that took place at 35 degrees C for 2-3 h (T2-T3), the cells developed forespores and their protein turnover was characterized by degradation of short-lived proteins and proteins made accessible to the proteolytic attack because of starvation. During the following irreversible sporulation phase refractile heat-resistant spores appeared at T4-T5. Protein turnover rate increased again after T2 and up to T8 60-70% prelabelled proteins were degraded. The SST suppressed sporulation at its beginning; at T3 no asymmetric septa were observed and the amount of heat-resistant spores at T8 was by 4-5 orders lower than at 35 degrees C. However, the cells remained viable and were able to sporulate when transferred to a lower temperature. Protein degradation was increased up to T3 but then its velocity sharply dropped and the amount of degraded protein at T8 corresponded to slightly more than one-half of that found at 35 degrees C. The cytoplasmic proteolytic activity was enhanced but the activity in the membrane fraction was decreased. When a temperature shift to SST was applied at the beginning of the irreversible sporulation phase (T2.5), the sporulation process was impaired. A portion of forespores lyzed, the others were able to complete their development but most spores were not heat-resistant and their coats showed defects. Protein degradation increased again because an effective proteolytic system was developed during the reversible sporulation phase but the amount of degraded protein was slightly lower than at 35 degrees C. A later (T4) shift to SST had no effect on the sporulation process.
Keywords: bakteriální proteiny; endopeptidasy; Temperature; Bacillus megaterium; spory bakteriální; kinetika; teplota; Endopeptidases; Spores, Bacterial; Bacterial Proteins; Kinetics